Ultrastructural and antioxidative changes in lupine embryo axes in response to salt stress - Łukasz Wojtyla; Magda Grabsztunowicz; Małgorzata Garnczarska (Acta Societatis Botanicorum Poloniae, 2013)
Embryo axes of lupine (Lupinus luteus L. ‘Mister’) were subjected to 0.1 M NaCl salt stress for 24 and 48 h. The ultrastructure modification and adjustment of antioxidant enzymes activities and izoenzymes profiles were observed. In cells of lupine embryo axes grown for 48 hours in medium with 0.1 M NaCl mitochondria took the forked shape and bulges of the outer mitochondrial membranes appeared. Moreover, the inflating and swelling of rough endoplasmic reticulum (RER) lumen and fragmentation of RER were noticed. The level of H2O2 was higher in salt treated embryo axes after 24 hours and increase of thiobarbituric acid reactive substances was observed after both 24 and 48 h of salt treatment. Native gel electrophoresis showed increased intensities of bands for catalase isozymes in response to salt stress, whereas activity of catalase was higher only in embryo axes grown for 48 h in control conditions. Appearance of two new isoforms of ascorbate peroxidase was observed after 48 h only under control condition, however increased activities were stated for both control and salt-stress condition after 48 h. No changes in isozymes pattern for superoxide dismutase were observed, but significant decrease in superoxide dismutase activity was noticed in relation to time and salt stress. Possible role of these enzymes in salt stress tolerance is discussed. The 0.1 M salt stress is regarded as a middle stress for lupine embryo axes and the efficiency of stress prevention mechanisms is proposed.